Cecal Volvulus in a child with congenital dilated cardiomyopathy: A case report. (2020) - Shehata, Ahmed E.; Helal, Mohamed A.; Ibrahim, EzzElDien A.; Magdy, Basma; El Seoudy, Mohamed; Shaban, Muayad; Taher, Heba
Highlights: Cecal volvulus is a very rare cause of intestinal obstruction in children. Novel association between Congenital dilated cardiomyopathy and cecal volvulus. Cecal volvulus should be suspected in a child presenting with bilious vomiting. Abstract: Introduction: Cecal volvulus is an extremely rare cause of intestinal obstruction in the pediatric age group and its incidence is unknown. Presentation of case: We present a unique case of cecal volvulus in a 3 year old female with congenital dilated cardiomyopathy. Discussion: Cecal mobility due to malfixation and malrotation is the main cause. Cecal Volvulus usually presents with constipation, abdominal pain and distention. Common complications entail strangulation, ischemia and gangrene. Cecal volvulus has been reported in association with various abnormalities. However, Incidence of cecal volvulus in a child with congenital dilated cardiomyopathy has not been reported. Surgery is the mainstay of management. Conclusion: Cecal volvulus should be kept in mind in a child presenting with signs suggestive of intestinal obstruction.